Memahami Spektrum Islam di Jawa - Muhammad Adlin Sila (Studia Islamika, 2011)
Book Review: Timothy Daniels, Islamic Spectrum in Java, England: Ashgate Publishing Limited, 2009. Ashgate e-book.Islam in Java has been a dominant theme within Indonesia's Islamic studies. For decades, the study on Islam in Java has indebted to the influential work of Clifford Geertz's The Religion of Java (1960). The work has become main reference for scholars and students interested in studying Islam in Java. Despite of many criticisms that have been addressed to Geertz's work, the typologies of socio-religious of Javanese Muslim-santri-priyayi-abangan-that was introduced by Geertz has stimulated other recent works on Javanese Islam. One of Geertz's celebrated argument is that Javanese Islam is syncretic. Mark Woodward (1989), another American anthropologist, concluding conversely, arguing that Javanese Islam is not syncretic but, it is a sufi Islam. In line with Woodward, Andrew Beatty (1999) added that those Javanese who involve in the traditional slametan ceremony participated in the ceremony because of the presence of brotherhood, not because of the similarity of their religious affiliation. The recent work of Timothy Daniels', the Islamic Spectrum in Java (2009) examines the variant of Javanese Islam much further.DOI: 10.15408/sdi.v18i3.430